Design and implementation of an inductor based cell balancing circuit with reduced switches for Lithium-ion batteries - R. Venkatasatish; C. Dhanamjayulu (Scientific Reports)
Abstract Electrical Vehicles (EVs) will eventually lead to reduced availability of fossil fuels and increased asset demand. The efficiency and range of electrically powered vehicles are influenced by the battery. The chemical structure of lithium-ion (LIB) batteries is particularly vulnerable to overcharging and deep discharge, which may damage the battery, reduce its life, and even cause dangerous things. Hence an efficient management system known as a battery management system (BMS) is needed to balance, protect, and manage the energy of the battery pack. Cell balancing is the most important of the three in terms of the longevity of the battery structure. Cells in a battery pack are imbalanced during charging and discharging due to the design parameters of cells in a battery pack which results in battery degradation and an increase in temperature. Hence efficient cell balancing techniques are needed to balance the battery pack to improve the safety level and life. Hence, the paper proposed a novel 2-layer multi-inductor active cell balancing (2 L MI-ACB) and single-layer multi-inductor active cell balancing with a state of charge-based controller. In the MATLAB/SimScape environment, the inductor-based balancing method for 52 V battery systems is implemented based on the comparison, and the results are explained. The model is tested with OPAL-RT 5700 real-time HIL Simulator and compared with simulation results to show its effectiveness.